The Influence of Regulatory Changes on Auditing Standards and Practices - Hanifah Hanifah; Edi Sutanto; Usep Siswadi; Muhammad Wahid Murniawan (Yayasan Adra Karima Hubbi, 2024)
Background. Regulatory changes have a profound effect on the auditing profession, impacting standards, practices, and the auditors’ role in ensuring financial transparency and accountability. As global financial markets evolve, regulatory bodies continue to update their frameworks to address new challenges, such as the increased complexity of financial reporting and the rise of digital technologies. Purpose. This study aims to explore the influence of regulatory changes on auditing standards and practices, specifically examining how these updates shape the audit process, redefine auditor responsibilities, and affect the overall effectiveness of audits in supporting corporate governance. Method. The research employs a mixed-methods approach, combining quantitative analysis of regulatory changes and auditing standards with qualitative insights gathered from interviews with auditing professionals. Data were obtained from publicly available regulatory updates and auditor feedback from multiple sectors, offering a comprehensive view of industry adjustments. Results. The findings indicate that regulatory changes significantly impact auditing practices, enhancing auditors' focus on risk management, ethical standards, and technology use in audits. Furthermore, auditors report a growing need for continuous professional development to keep up with regulatory advancements, highlighting the profession's need for agility and ongoing learning. Conclusion. This study concludes that regulatory changes are crucial for enhancing auditing standards and ensuring the relevance and efficacy of audits in a rapidly evolving financial landscape. Continuous adaptation to these updates is essential for auditors to maintain their role in safeguarding financial integrity. The research suggests that both regulatory bodies and auditing firms should collaborate to provide continuous education and resources to help auditors meet the profession’s evolving demands.